Synthetic peptides from heat‐shock protein 65 inhibit proinflammatory cytokine secretion by peripheral blood mononuclear cells from rheumatoid arthritis patients. (January 2014) - Zhou, Jun; Wang, Li‐Ping; Feng, Xuan; Fan, Dan‐Dan; Zang, Wei‐Jin; Wang, Bing
Summary Rheumatoid arthritis (RA) is a systemic autoimmune disease mediated by T cells. Proinflammatory cytokines plays a critical role in the pathogenesis of RA. The aim of the present study was to investigate the effects of synthetic peptides (HP‐R1, HP‐R2 and HP‐R3), derived from the sequence of 65 kDa mycobacterial heat shock protein (HSP), on the proliferation of and cytokine secretion by peripheral blood mononuclear cells (PBMC) from RA patients. The PBMC were obtained from RA patients and collected by Ficoll‐Hypaque density centrifugation. Peripheral blood mononuclear cells were treated with one of the three synthetic peptides for 4 h, after which time proliferation and cytokine production were determined. The effects of the three peptides on the proliferation of PBMC were analysed by the colorimetric cell proliferation (CCK‐8) assay. Cytokine production was measured in culture supernatants using specific ELISAs. None of the three peptides had any significant effect on the proliferation of PBMC from healthy controls. However, the proliferation of PBMC from RA patients was inhibited by all three peptides. The production of tumour necrosis factor‐α from RA patients was significantly inhibited by all three peptides. The secretion of interferon‐γ was significantly suppressed by HP‐R1 and HP‐R2. Unlike the other two peptides, HP‐R2 increased the secretion of interleukin (IL)‐4. None of the peptides had any significant effect on the production of IL‐10. The results of the present study suggest that the synthetic peptides derived from HSP65 exhibit antiproliferative and anti‐inflammatory activity, and support the potential use of synthetic peptides as therapeutic drugs in RA patients.